2018
DOI: 10.1158/1078-0432.ccr-18-0304
|View full text |Cite
|
Sign up to set email alerts
|

Increased Synthesis of MCL-1 Protein Underlies Initial Survival of EGFR-Mutant Lung Cancer to EGFR Inhibitors and Provides a Novel Drug Target

Abstract: EGFR inhibitors (EGFRi) are effective against -mutant lung cancers. The efficacy of these drugs, however, is mitigated by the outgrowth of resistant cells, most often driven by a secondary acquired mutation in EGFR, We recently demonstrated that can arise during treatment; it follows that one potential therapeutic strategy to thwart resistance would be identifying and eliminating these cells [referred to as drug-tolerant cells (DTC)] prior to acquiring secondary mutations like We have developed DTCs to EGFRi i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 68 publications
1
35
0
Order By: Relevance
“…Regarding treatment, the development of EGFR- tyrosine kinase inhibitors (EGFRi) resulted in some success, but the observed responses were short, due to the development of acquired resistance resulting from secondary or tertiary EGFR mutations and other mechanisms [ 52 ]. After exposure to EGFR inhibitors, EGFR-mutant NSCLC cells lose their ability to undergo apoptosis, partially due to the high expression of MCL-1 and finally become “drug-tolerant cells.” This overexpression is explained by (1) enrichment of cells with preexisting high MCL-1 expression and (2) activation of the mTORC1/eIF4E-mediated cap-dependent translation pathway that controls MCL-1 expression [ 52 ]. Combining MCL-1 and EGFR inhibitors synergistically reduced viability, induced apoptosis and prevented the development of drug-tolerant cells.…”
Section: Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding treatment, the development of EGFR- tyrosine kinase inhibitors (EGFRi) resulted in some success, but the observed responses were short, due to the development of acquired resistance resulting from secondary or tertiary EGFR mutations and other mechanisms [ 52 ]. After exposure to EGFR inhibitors, EGFR-mutant NSCLC cells lose their ability to undergo apoptosis, partially due to the high expression of MCL-1 and finally become “drug-tolerant cells.” This overexpression is explained by (1) enrichment of cells with preexisting high MCL-1 expression and (2) activation of the mTORC1/eIF4E-mediated cap-dependent translation pathway that controls MCL-1 expression [ 52 ]. Combining MCL-1 and EGFR inhibitors synergistically reduced viability, induced apoptosis and prevented the development of drug-tolerant cells.…”
Section: Solid Tumorsmentioning
confidence: 99%
“…Combining MCL-1 and EGFR inhibitors synergistically reduced viability, induced apoptosis and prevented the development of drug-tolerant cells. This combination also reduced subcutaneous tumors in xenograft models with EGFR-mutated cell lines [ 52 ].…”
Section: Solid Tumorsmentioning
confidence: 99%
“…EGF promotes Mcl-1 expression by increase Mcl-1 transcription in an Elk-1 transcription factor-dependent manner 10 . EGFR mutant NSCLC cells upregulate Mcl-1 through mTORC1-mediated mRNA translation, which contributes to EGFR TKI resistance 11 . Moreover, inhibition of EGFR by shRNA or erlotinib disrupts Bim binding to Mcl-1 and restoring the sensitivity to ABT-737 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent study has shown that the natural product, bufalin, can reverse acquired resistance to Osim through induction of Ku70‐mediated Mcl‐1 degradation (Cao et al , ). Moreover, it has been shown that EGFR‐mutant NSCLC cells tolerated to short‐term EGFR‐TKI treatment possess elevated Mcl‐1 levels and can be sensitized to EGFR‐TKIs by targeting Mcl‐1 (Song et al , ). These studies together with our findings here thus highlight critical involvement of Mcl‐1 in the development of acquired resistance to EGFR‐TKIs including Osim and suggest a possible strategy for delaying and/or overcoming acquired resistance to Osim by co‐targeting Mcl‐1.…”
Section: Discussionmentioning
confidence: 99%